Identifikasi Kandungan Karbohidrat dalam Bahan Pangan menggunakan Metode Uji Benedict dan Lugol - Marpaung, Mauritz Pandapotan; Prasetyo, Dani (JOURNAL OF HEALTH SCIENCE, 2025)
Carbohydrate content in food has nutritional content as the main source of energy that is needed by the body in carrying out metabolism. The purpose of this experiment is to qualitatively analyze the carbohydrate content in various foodstuffs through the Benedict and Lugol tests. The food materials identified were bananas, potatoes, honey, cassava, milk, green beans, corn, apple cider, rice and white bread. The results of the experiment showed that all food ingredients showed positive results for reducing sugar in the Benedict test. While positive results in the Lugol (iodine) test were found in bananas, potatoes, cassava, green beans, corn, and bread. The Benedict test aims to identify the presence of sugars that can reduce aldehyde and ketone groups while the Lugol (iodine) test aims to identify the presence of polysaccharides (complex carbohydrates).